Agriculture, a strategic issue : report of the state of and outlook for agriculture and rural life in the Americas 2005 : executive summary (IICA San JoseCR, 2004)
Notes the importance and future of agriculture. Highlights critical issues underpinning the regional context and examines the performance of agriculture. Opines that problems and concerns continue to exist. Deals with the challenges and outlook for agriculture and rural life.
Bibliography: p. 49-51